Invitation to a murder [videorecording (DVD)] - O'Donnell, Brian; Miller, Gerard; Barton, Mischa; Browning, Chris; Santos, Bianca A., 1990-; Urbaniak, James, 1963-; Matthey, Giles, 1987-; Kung, Grace Lynn; Sloan, Amy, 1978-; Dever, Seamus, 1976-; Hyde-White, Alex, 1959- (Lionsgate, 2023)
In this homage to Agatha Christie, set in England, an amateur detective finds herself caught up in a real-life whodunit! Miranda Green is summoned to the remote mansion of billionaire Lewis Findley along with five mysterious strangers. What do they all have in common? What's become of their absent host? And who just murdered one of the guests in cold blood? Now Miranda must hunt for hidden clues, interview witnesses, and find the killer before she becomes the next victim.